2010
DOI: 10.1111/j.1462-5822.2010.01535.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined action of the type IV secretion effector proteins BepC and BepF promotes invasome formation of Bartonella henselae on endothelial and epithelial cells

Abstract: Summary Bartonella henselae (Bhe) can invade human endothelial cells (ECs) by two distinguishable entry routes: either individually by endocytosis or as large bacterial aggregates by invasome‐mediated internalization. Only the latter process is dependent on a functional VirB/VirD4 type IV secretion system (T4SS) and the thereby translocated Bep effector proteins. Here, we introduce HeLa cells as a new cell system suitable to study invasome formation. We describe a novel route to trigger invasome formation by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(84 citation statements)
references
References 35 publications
(80 reference statements)
2
82
0
Order By: Relevance
“…1B,C). Among these positively validated genes of the secondary screen were the small GTPases Cdc42 and Rac1, which were previously shown to contribute to invasome formation and therefore served as internal positive controls Truttmann et al, 2011). Furthermore, we identified the two tyrosine kinases Src and FAK, as well as the transmembrane receptor integrin b1, and the adaptor proteins paxillin, talin1 and vinculin as novel components essential for invasome formation.…”
Section: Several Components Associated With Integrin-mediated Signalimentioning
confidence: 92%
See 1 more Smart Citation
“…1B,C). Among these positively validated genes of the secondary screen were the small GTPases Cdc42 and Rac1, which were previously shown to contribute to invasome formation and therefore served as internal positive controls Truttmann et al, 2011). Furthermore, we identified the two tyrosine kinases Src and FAK, as well as the transmembrane receptor integrin b1, and the adaptor proteins paxillin, talin1 and vinculin as novel components essential for invasome formation.…”
Section: Several Components Associated With Integrin-mediated Signalimentioning
confidence: 92%
“…The Bep proteins trigger all known VirB/D4-associated phenotypic changes of infected endothelial cells (ECs), including (1) inhibition of apoptosis, (2) activation of an NF-kB-dependent pro-inflammatory response, (3) capillary-like sprout formation of ECs embedded in a 3D matrix, and (4) bacterial invasion of ECs as well as epithelial cells by a unique cellular structure termed the invasome (Schmid et al, 2004;Schmid et al, 2006;Rhomberg et al, 2009;Scheidegger et al, 2009;Selbach et al, 2009). Invasome formation has been shown to depend on the translocation of BepG or the combination of BepC and BepF into the recipient cells Truttmann et al, 2011). Bhe internalization by the invasome route is a tightly controlled process, consisting of initial adherence, effector protein translocation, the formation of bacterial clusters and engulfment by plasma-membrane-derived membrane protrusions, eventually resulting in the complete internalization of the bacterial aggregates Rhomberg et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in vitro experiments have indicated that VirB/D4 and its effector proteins mediate a range of profound changes to parasitised endothelial cells [50,51], including (i) massive rearrangements of the actin cytoskeleton, resulting in the formation and internalisation of large bacterial aggregates by a unique “invasome” structure, (ii) NF-κβ-dependent pro-inflammatory activation leading to cell adhesion molecule expression and chemokine secretion, and (iii) inhibition of apoptotic cell death resulting in enhanced endothelial cell survival. Internalisation of bartonellae via invasomes (characterised by the formation of a bacterial aggregate on the cell surface, which is subsequently engulfed and internalised by an actin-dependant mechanisms [26]) is dependent on three VirB/D4 effectors, BepC, BepG, and BepF [52,53]. BepA has been shown to inhibit endothelial cell apoptosis through upregulation of cAMP levels in the cytosol [49] and it also promotes capillary sprout formation in an endothelial spheroid infection model, whereas BepG inhibits such sprouting [54].…”
Section: Step 1: Infection Prior To Bacteraemiamentioning
confidence: 99%
“…2) Truttmann et al 2011b). This process is dependent on integrin-b1 (ITGB1) binding and activation via Talin-1 inside-out signaling and on integrin-b1-mediated outside-in signaling by focal adhesion kinase (FAK), Src, vinculin, and paxilin (Truttmann et al 2011b). Invasome rearrangement of the F-actin cytoskeleton involves Arp2/3-dependent cortical F-actin polymerization by Rac1/Scar1/WAVE, Cdc42/ WASP pathways, and additionally by cofilin-1 in the case of BepC and BepF Truttmann et al 2011b,c).…”
Section: Lessons Learned From In Vitro Studiesmentioning
confidence: 99%
“…In each case, this results in the formation of a compact F-actin ring composed of condensed stress fibers, and membrane protrusions on the host-cell surface (Fig. 2) Truttmann et al 2011b). This process is dependent on integrin-b1 (ITGB1) binding and activation via Talin-1 inside-out signaling and on integrin-b1-mediated outside-in signaling by focal adhesion kinase (FAK), Src, vinculin, and paxilin (Truttmann et al 2011b).…”
Section: Lessons Learned From In Vitro Studiesmentioning
confidence: 99%